Preparação e caracterização de um candidato à material de referência de elementos traço em petróleo - Marchezi, Thabita Thiciana Bastos (2019)
Due to the complexity determination of trace elements in crude oil, mainly by multi element techniques, many works have been developed to optimize instrumental parameters and new techniques for preparation and introduction of samples, aiming at improving the sensitivity, precision and accuracy in the measurement. In all cases, it is necessary to use reference materials (RMs) and/or certified reference materials (CRMs) to verify the performance of the new proposed method. However, most reference materials for trace elements in the liquid fuels are matrices like gasoline, diesel oil, fuel oil and lubricating oil. In this work it was developed all the necessary steps for the preparation, characterization and certification of a national crude oil reference material for trace elements following the internationally accepted requirements. Three kilos of crude oil were homogenized under optimized conditions and they were distributed among 115 units containing about 20 g each. The homogeneity of the material was studied in the different units produced. For the short term stability study, a test was performed at different temperatures, ranging from + 4 to + 50 º C, and storage times of 1, 2, 3 and 4. The long-term study was performed for 9 months at the laboratory room temperature (+20 to +26 ºC). The obtained results indicated that the material was homogeneous and stable under the studied conditions. For the statistical evaluation, classical statistical techniques were performed, such as analysis of variance and regression tests and multivariate techniques, as the principal component Analysis (PCA). For the values attributed to the mass fractions (µg g-1), a multi-method in-house approach was used. The combination of the results obtained in the characterization and in the studies of homogeneity and stability allowed to assign values to 5 elements with their respective uncertainties: 2 certified values (Ni and V), 3 reference values (Ba, Na and Sr) and 4 values information (Ca, Mg, Co and Fe).